Large-scale synthesis of 2D metal dichalcogenides. Issue 17 (25th April 2018) - Yu, Jing; Hu, Xiaozong; Li, Huiqiao; Zhou, Xing; Zhai, Tianyou
Abstract : In this review, we focus on the large-scale synthesis of 2DMDs via mechanical exfoliation, liquid phase method and CVD process. Abstract : In recent years, 2D metal dichalcogenides (2DMDs, MX2 : M = Mo, W, Re, Nb; X = S, Se, Te, etc. ) have attracted significant attention due to their diverse properties such as tunable bandgaps and valley polarization, showing highly promising applications in electronics and optoelectronics. For practical applications, the large-scale synthesis of 2DMDs is indispensable and therefore requires urgent research. In this review, the latest methods for the large-scale synthesis of 2DMDs are introduced including mechanical exfoliation, liquid phase methods and chemical vapour deposition (CVD). The CVD process can be classified as follows: direct growth via vapour phase deposition, chalcogenization of the deposited films of metal precursors on the substrate, and synthesis of large-scale 2DMDs on the treated substrate and on the molten substrate. Finally, some perspectives are provided for this exciting and fast-developing field, which indicate that the major existing obstacles preventing practical applications are the limited domain size, crystallinity, layer controllability and universality of the synthesis methods.